(untitled) (Bulletin of Kharkiv National University of Internal Affairs, 2022)
In today’s difficult conditions, the issue of clarifying and improving the basic principles of regulating labor protection relations, including in the field of labor protection, is gaining considerable relevance. All this leads to additional attention being paid to the principles as initial provisions that determine the nature and essence of a certain social phenomenon (in our case – legal regulation of the field of labor protection). The task of the work is an in-depth analysis of the place of principles in the science of labor law and substantiation of directions for improvement of the principle basis of legal regulation of labor protection measures. Various approaches to the application of principles in the field of legal regulation of social labor relations and labor protection are analyzed. It is noted that the principles indicate the essential features of the legal regulation of social and labor relations, that they form the foundation of current and prospective legislation in the field of labor law. It is natural that these principles are specified and acquire the status of legal norms in laws and by-laws. Therefore, it should be about a kind of chain: from the principles to their application in normative legal acts. Some shortcomings in the content of the principles, which require urgent correction, were also noted. The statement that the process of formation and implementation of principles requires urgent improvement is substantiated. The problem of properly enshrining the principles in normative legal acts on labor protection is urgent. First of all, it should be noted the insufficient degree of validity of some of the formally defined principles. The process of improving legal policy in the field of labor protection should be systematic and interconnected: from principles to general and special norms.